Über die Bedeutung des Humus für Bodenerosion und Hangstabilität in den feuchten und wechselfeuchten Tropen von Papua Neuguinea - Klaer, Wendelin; Krieter, Manfred (ERDKUNDE, 1982)
When assessing the risk of erosion in a given area, the factor of slope inclination, intensity of precipitation and soil utilization are generally held to be of great importance. This would permit the conclusion that the effect of erosion must assume catastrophic proportions in those places where these factors themselves that contribute to the process have extremely negative dimensions. But, surprisingly enough, the steeply inclined slopes in the high lands of Papua-New Guinea, though exposed to the most violent tropical thunder showers, do not show any soil erosion worth mentioning in their exposed agricultural areas. Even the cultivation savannas with but few species are not prone to erosion. The decisive factor in this totally unexpected, extraordinary stability of slopes against erosion in the humid tropics of Papua-New Guinea, is the regulatory role played by the top-soil, which - against all normal expectation - quite untypically owes its high degree of permeability and structural stability to its high humus content. When the organic substance is missing, as is the case in the sub-soils or in the overall soil profile of the marginally tropical and periodically humid zone of Papua-New Guinea, devastating soil erosion is part of the normal inventory of morphodynamics. Together with the frequency of humus layers on the island, slope stability and erosion decrease sharply from the zone of the periodically humid tropics as a result of increased oxidization processes during the dry season, which extends over several months. In future considerations of the improvement of soil fertility control importance will also have definitely to be accorded to the outstanding position of humus in soil stability.